Founder team prior work experience: An asset or a liability for startup growth? - Hashai, Niron; Zahra, Shaker (Strategic Entrepreneurship Journal, 2022)
Abstract Research Summary We examine the effects of founder teams' firm‐ and industry prior work experience on startup growth in the context of high technology industries. We study these effects both on the early growth of startups and on their growth, after accumulating experiential knowledge. Integrating the literatures on human capital, imprinting and competency traps, we develop a typology of four combinations of founder prior experience: founder same firm and same industry experience, founder same industry but other firm experience, founder same firm but other‐industry experience, and founder other‐industry and other firm experience. Using data from 153 Israeli high technology startups, we find significant variations in the effects of these combinations on startup growth, which also vary between the early and later years of these startups. Managerial Summary Founders play a key role in the lives of their startups, applying their resources, knowledge and experience. Therefore, we ask: how does founder experience influence high technology startups' growth? To answer this question, we examine four combinations of founder prior experience: founder same firm and same industry experience, founder same industry but not same firm experience, founder same firm but other‐industry experience, and founder other‐industry and not same firm experience. Our analyses show significant differences in startup growth based on these combinations of founder prior experience and, importantly, the effect of these four combinations on startups' growth in their early years of existence differs significantly from later years, when these firms can increasingly draw on their own experiential learning.